2007
DOI: 10.3748/wjg.v13.i6.950
|View full text |Cite
|
Sign up to set email alerts
|

Detection of aberrant methylation in fecal DNA as a molecular screening tool for colorectal cancer and precancerous lesions

Abstract: AIM: To i nve s t i g a t e t h e fe a s i b i l i ty o f d e t e c t i n gmethylated fecal DNA as a screening tool for colorectal carcinoma (CRC) and precancerous lesions. METHODS:Methylated secreted frizzled-related protein gene 2 (SFRP2 ), hyperplastic polyposis protein gene (HPP1 ) and O 6 -methylguanine-DNA methyltransferase gene (MGMT ) in stools from 52 patients with CRC, 35 patients with benign colorectal diseases and 24 normal individuals were analyzed using methylation-specific PCR.RESULTS: Methylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 18 publications
3
74
1
Order By: Relevance
“…Detection of CpG island methylation in human DNA isolated from stool (Belshaw et al, 2004;Leung et al, 2004;Chen et al, 2005;Zitt et al, 2007) or serum (Zou et al, 2002;Leung et al, 2005;Nakayama et al, 2007;Lofton-Day et al, 2008) has been proposed as a new strategy for the early diagnosis of colorectal neoplasia. Other studies with comparable series have reported high sensitivities for different methylation markers used alone (Chen et al, 2005;Lenhard et al, 2005;Huang et al, 2007a;Wang and Tang, 2008) or in combination (Leung et al, 2004;Petko et al, 2005;Huang et al, 2007b;Lofton-Day et al, 2008), although a wider application is usually hinder by a limited specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of CpG island methylation in human DNA isolated from stool (Belshaw et al, 2004;Leung et al, 2004;Chen et al, 2005;Zitt et al, 2007) or serum (Zou et al, 2002;Leung et al, 2005;Nakayama et al, 2007;Lofton-Day et al, 2008) has been proposed as a new strategy for the early diagnosis of colorectal neoplasia. Other studies with comparable series have reported high sensitivities for different methylation markers used alone (Chen et al, 2005;Lenhard et al, 2005;Huang et al, 2007a;Wang and Tang, 2008) or in combination (Leung et al, 2004;Petko et al, 2005;Huang et al, 2007b;Lofton-Day et al, 2008), although a wider application is usually hinder by a limited specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to compare these panels and kits and discover their advantages and limitations. Ultimately, the tion of CRC and a small number of advanced adenomas reached a sensitivity and specificity of 96% [58] . A followup study found that SFRP2 methylation was detectable in the stool of almost half of all patients with hyperplastic polyps or colorectal adenomas [53] , further supporting its use in the detection of premalignant lesions.…”
Section: Biomarkers Of Dna Methylation In Bloodmentioning
confidence: 99%
“…Loss of SFRP2 expression due to promoter methylation has been frequently observed in many tumors, including colorectal, ovarian, breast, gastric and liver cancers [17,[20][21][22][23]. Several earlier studies have demonstrated that the frequency of SFRP2 promoter methylation in fecal DNA is markedly increased in CRC patients compared with normal healthy controls [24][25], suggesting the SFRP2 hypermethylation in fecal DNA as a potential molecular biomarker of CRC. In this study, we extended the previous work and systematically evaluated the diagnostic potentials of SFRP2 promoter methylation in tumor tissue, stool and serum DNA samples in CRC.…”
Section: Resultsmentioning
confidence: 99%